2019
DOI: 10.1590/fst.18918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of resistant starch in sausage with fat reduction on the physicochemical and sensory properties

Abstract: Sausage is one of the meat products most consumed in Brazil, although the incorporation of fat is necessary for its elaboration, influencing its technological and sensory characteristics and its caloric value. The aim of this study was to evaluate the addition of resistant starch as a fat substitute in sausage on physicochemical properties and sensory acceptance. The analyses performed were the centesimal composition, emulsion stability, instrumental colour, texture profile analysis and sensorial acceptance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Likewise, the addition of quinoa flour in frankfurter sausage significantly increased colour intensity of the product [90]. On the contrary, the resistance starch addition had no influence on the sausage colour [91]. In this study, addition of MPP had considerably altered the colour of Chinese sausage due to the bioactive compounds, especially carotenoid consisting in ripe mango peel [34,92,93].…”
Section: Colourmentioning
confidence: 52%
See 1 more Smart Citation
“…Likewise, the addition of quinoa flour in frankfurter sausage significantly increased colour intensity of the product [90]. On the contrary, the resistance starch addition had no influence on the sausage colour [91]. In this study, addition of MPP had considerably altered the colour of Chinese sausage due to the bioactive compounds, especially carotenoid consisting in ripe mango peel [34,92,93].…”
Section: Colourmentioning
confidence: 52%
“…The highest and lowest values obtained were for 0% and 15% (w/w) of the pectin supplementation, respectively. Garcia-Santos et al [91] revealed that the sausage with the addition of resistant starch had a low value of cohesiveness (0.50-0.70). Choe et al [100] also reported the cohesiveness values of sausages supplemented with wheat fibre for the reduction of fat ranged from 0.27 to 0.34.…”
Section: Texturementioning
confidence: 99%
“…The researchers observed that partial replacement of the adipose tissue with resistant starch up to 5% reduced the calorific value of the product, improved the stability of the emulsion, its colour parameters and texture profile. The modified sausages were accepted by consumers [ 53 ]. Pereira et al investigated the effect of rice flour, glutinous rice flour, and tapioca starch on the stability of emulsion, moisture, protein secondary structure and the microstructure of cooked emulsified sausage.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting substantial type of starch in a green banana is the resistant starch (RS), which is not digested in the stomach and small intestine, but is passed on to be fermented by microbiota bacteria, producing shortchain fatty acids and other organic acids in the large intestine. RS does not supply glucose to the body, is related to a decreased GI of carbohydrates (Garcia- Santos et al, 2019). A low GI can help keep blood sugar levels stable, and has been associated with weight control and decreased risk of developing diabetes (Annison & Topping, 1994).…”
Section: Introductionmentioning
confidence: 99%